Scaffolding Metakognitif dalam Pembelajaran Matematika untuk Meningkatkan Literasi Matematika Siswa - Nasir, Norma; Khadijah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
Students’ mathematical literacy remains relatively low, particularly in understanding, modeling, and solving contextual problems. This study aims to examine the effectiveness of metacognitive scaffolding in mathematics instruction to improve students’ mathematical literacy. A quasi-experimental method with a nonequivalent control group design was employed, conducted at MA Arifah Gowa, involving two classes consisting of 30 students each. The experimental group received instruction integrated with metacognitive scaffolding, while the control group was taught using conventional methods. The instruments included a mathematical literacy test and an observation sheet of metacognitive activities. Data were analyzed using descriptive and inferential statistics. The results show that the mean pretest scores of the experimental and control groups were 41.27 and 40.85, respectively, indicating comparable initial abilities. After the treatment, the mean posttest score of the experimental group increased to 78.45 (high category), while the control group reached 61.32 (medium category). The difference in improvement between the two groups was 17.13 points. The independent t-test revealed that t = 4.276 > 1.67 with p = 0.000 < 0.05, indicating a significant difference between the groups. These findings indicate that metacognitive scaffolding facilitates students’ ability to plan, monitor, and evaluate their thinking processes, leading to better problem-solving performance and more consistent learning outcomes. Metacognitive scaffolding is therefore an effective instructional approach for enhancing students’ mathematical literacy.